2019
DOI: 10.1093/rheumatology/kez242
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine treatment downregulates systemic interferon activation in primary Sjögren’s syndrome in the JOQUER randomized trial

Abstract: ObjectiveHCQ is frequently used to treat primary SS (pSS), but evidence for its efficacy is limited. HCQ blocks IFN activation, which is present in half of the pSS patients. The effect of HCQ treatment on the expression of IFN-stimulated genes (ISGs) was studied in pSS. Furthermore, HCQ-treated patients were stratified based on IFN activation and differences in disease activity and clinical parameters were studied.MethodsExpression of ISGs and IFN scores was determined in 77 patients, who were previously enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 14 publications
1
42
1
2
Order By: Relevance
“…In a third large observational study from the UK, conducted in 608 patients with primary SS, patients with the lowest symptom burden had the highest expression of IFN‐inducible genes (25). In a recent clinical study of hydroxychloroquine for the treatment of primary SS, it was observed that hydroxychloroquine treatment resulted in a significant decrease in IFN‐inducible gene expression, but no clinical improvement (26).…”
Section: Discussionmentioning
confidence: 99%
“…In a third large observational study from the UK, conducted in 608 patients with primary SS, patients with the lowest symptom burden had the highest expression of IFN‐inducible genes (25). In a recent clinical study of hydroxychloroquine for the treatment of primary SS, it was observed that hydroxychloroquine treatment resulted in a significant decrease in IFN‐inducible gene expression, but no clinical improvement (26).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of side effects is only 10.9% 27,28 . A placebo‐controlled JOQUER trial showed that hydroxychloroquine (HCQ) reduced the levels of type I IFNs and IFN‐stimulated genes in peripheral blood of pSS patients, as well as reducing inflammatory markers, although it did not improve disease activity 29 . HCQ causes varying degrees of ocular toxicity and retinal damage, a number of clinical studies have developed a safe dose range and protocols to decrease adverse reactions 30 .…”
Section: Managementmentioning
confidence: 99%
“…The net effect of such inhibition is the suppression of antigen-presenting cell activity, decreased autoantibody secretion and decreased activity of NF-κB and levels of PIC production [ 115 , 120 , 121 , 123 , 124 ], (reviewed by [ 125 ]). Characteristic changes in immune and inflammatory profiles induced by hydroxychloroquine therapy typically involve reductions in IL-1β, IL-6, TNF-α, CXCL-10, sCD40L and interferon-α (IFN-α2) [ [115] , [116] , [117] , 123 , 124 , [126] , [127] , [128] ]. Hydroxychloroquine therapy may also reduce B cell activity [ 129 ] and Th17 cell differentiation [ 130 , 131 ], while promoting a Th1 to Th2 transition [ 130 ] and inhibiting the production of the PICs CCL2 and CXCL10 [ 132 ].…”
Section: Hydroxychloroquinementioning
confidence: 99%